Penguatan Nilai-Nilai Ketahanan Nasional Di Sekolah Melalui Pendidikan Kewarganegaraan (Studi Di SMK Pusdikhubad Kota Cimahi, Jawa Barat) - Lili Halimah; Anis Suryaningsih Suryaningsih; Yayuk Hidayah; Risti Aulia Ulfah (Jurnal Ketahanan Nasional, 2021)
ABSTRACT             The idea of the strengthening of citizenship values came with implications on the perspective of realizing national resilience in the school. The purpose of this study was to analyzed the strengthening of citizenship values to realized national resilience in the School environment.                 This research used a qualitative approach with a case study design. Data collection used interview, observation and documentation techniques. Data analysis used interactive analysis consisting of data reduction, data presentation and data verification.                 The results showed that strengthening the values of citizenship to realized national resilience in the school environment was through three ways, namely: 1) learning innovative citizenship education, 2) internationalizing the values of national resilience in the school environment by habituation and 3) the existence of extracurricular activities which was a discussion forum for students to deepened the values of national resilience in the school environment. Citizenship values were important for students because they would form a person who had a national spirit, loves the motherland and had an identity as an Indonesian nation.         ABSTRAK Gagasan penguatan  nilai-nilai kewarganegaraan hadir dengan implikasi pada perspektif  mewujudkan ketahanan nasional pada lingkungan sekolah. Tujuan penelitian ini menganalisis penguatan nilai-nilai kewarganegaraan dalam mewujudkan ketahanan nasional pada lingkungan sekolah.Penelitian ini menggunakan pendekatan kualitatif dengan disain studi kasus. Pengumpulan data menggunakan teknik wawancara, observasi dan dokumentasi. Analsisi data menggunakan analisis interaktif yang terdiri dari reduksi data, penyajian data dan verifikasi data.Hasil penelitian menunjukkan bahwa penguatan nilai-nilai kewarganegaraan untuk   mewujudkan ketahanan nasional pada lingkungan sekolah dilakukan melalui tiga cara, yaitu: 1) pembelajaran pendidikan kewarganegaraan yang inovatif, 2) internasliasi nilai-nilai ketahanan nasional pada lingkungan sekolah dengan pembiasaan dan 3) adanya aktivitas ekstra kurikuler yang menjadi forum diskusi bagi siswa dalam memperdalam nilai-nilai ketahanan nasional pada lingkungan sekolah. Nilai-nilai kewarganegaraan penting bagi siswa karena akan membentuk pribadi yang memiliki jiwa nasioalisme, cinta tanah air dan memiliki identitas sebagai bangsa Indonesia.